2014
DOI: 10.1259/bjr.20140354
|View full text |Cite
|
Sign up to set email alerts
|

The role of multidetector-row CT in the diagnosis, classification and management of acute aortic syndrome

Abstract: The term "acute aortic syndrome" (AAS) encompasses several non-traumatic life-threatening pathologies of the thoracic aorta presenting in patients with a similar clinical profile. These include aortic dissection, intramural haematoma and penetrating atherosclerotic ulcers. These different pathological entities can be indistinguishable on clinical grounds alone and may be confused with other causes of chest pain, including myocardial infarction. Multidetector-row CT (MDCT) is the current modality of choice for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 85 publications
1
17
0
Order By: Relevance
“…Recently, it was shown that using the heavily T1‐weighted sequence on MRI could increase the reliability of detection of intramural hematoma compared with using the T1‐fat saturation method, which could improve the accuracy of vertebral artery dissection diagnosis . In aortic dissection, multi‐detector row CT is the modality of choice for imaging acute aortic syndrome with a sensitivity and specificity approaching 100% …”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that using the heavily T1‐weighted sequence on MRI could increase the reliability of detection of intramural hematoma compared with using the T1‐fat saturation method, which could improve the accuracy of vertebral artery dissection diagnosis . In aortic dissection, multi‐detector row CT is the modality of choice for imaging acute aortic syndrome with a sensitivity and specificity approaching 100% …”
Section: Discussionmentioning
confidence: 99%
“…Recent standard of multi-detector rows is 64-rows system. 7,8) With helical scanning technique, such CT scanners have wide z-axis coverage in one scan with single breathholding. High-end scanners with 128 or more rows 9) also have the potential to shorten the scan duration, improve spatial resolution, and/or scan an organ in a single gantry rotation without moving the patient s table.…”
Section: Multi-detector Rowsmentioning
confidence: 99%
“…CT angiography has a sensitivity and specificity approaching 100% (ref. 3 ). CT angiography protocol used by the authors includes: 1.…”
Section: Acute Aortic Syndromementioning
confidence: 99%